The effect of systematically created success situations on learning motivation among primary school students - Sabila Abzhanova; Gulnar Uaisova; Madina Togatay; Aliya Jakhayeva; Nazymkul Altayeva; Saule Zhorayeva (Institute of Advanced Engineering and Science, 2026)
Learning motivation is a critical factor influencing students’ academic engagement, persistence, and long-term educational outcomes. In primary education, motivation is particularly important, as early learning experiences shape children’s attitudes toward school and their willingness to participate in academic activities. The aim of this study was to examine the impact of systematically created success situations on learning motivation among primary school students in Kazakhstan. The study involved 72 participants. A quasi-experimental design was employed, with students participating in a six-week intervention structured to provide frequent success experiences, while a comparison group continued regular classroom instruction. Motivation was assessed before and after the intervention using selected subscales of the intrinsic motivation inventory, including interest/enjoyment, perceived competence, and effort/importance. The results indicated significant improvements in all measured dimensions of motivation for students who experienced the intervention compared with the comparison group. Increases were observed in students’ perceived competence, engagement with learning activities, and willingness to invest effort. These findings suggest that systematically creating opportunities for success is an effective approach to enhancing learning motivation in primary education and provide practical guidance for classroom implementation.